2000
DOI: 10.1023/a:1005573031757
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The present study was designed to examine the relationship between unconventionality and marijuana use over time. The sample for this paper consisted of 532 male and female participants interviewed during early adolescence, late adolescence, their early twenties, and their late twenties. Latent growth modeling was used. The findings indicated that (1) the influence of initial unconventionality (T2) on initial marijuana use (T2) was stronger for males, (2) unconventionality at T2 was not significantly related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…21,22,30,67,18,20 Few examine other illicit drugs, how the choice of substances changes with age, and the sequences of multiple SUDs. Thus, we have the fewest data on the most serious patterns of abuse.…”
Section: Discussionmentioning
confidence: 99%
“…21,22,30,67,18,20 Few examine other illicit drugs, how the choice of substances changes with age, and the sequences of multiple SUDs. Thus, we have the fewest data on the most serious patterns of abuse.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests a link between childhood aggression, drug use, and later delinquency mediated by early conduct disorder (Brook, Whiteman, Finch, & Cohen, 1995Dobkin, Tremblay, Masse, & Vitaro, 1995 ;Hawkins, Catalano, & Miller, 1992 ;Kellam, Brown, Rubin, & Ensminger, 1983 ;Robins & McEvoy, 1990 ;Robins & Wish, 1977 ;Stacy & Newcombe, 1995). In keeping with this, longitudinal studies (conducted in the 1980s) reported childhood personality attributes such as aggression, a '' difficult '' temperament, rebelliousness, impulsivity, mood disturbances, and interpersonal difficulties to be related to later drug use (Block, Block, & Keyes, 1988 ; J.…”
Section: Aetiologymentioning
confidence: 99%